A community-based survey of malaria and its prevention in Jazan, Saudi Arabia. Issue 1 (2nd January 2020) - Tripathi, Rina; Makeen, Hafiz A.; Albarraq, Ahmed A.; Tripathi, Pankaj; Meraya, Abdulkarim M.; Mubaraki, Amal A.; Alfaifi, Mashael E.
ABSTRACT: Background : The fight against malaria has been effective globally and Saudi Arabia is in the stage of malaria pre-elimination to nearly complete elimination. Aim: The current study assesses the level of knowledge, attitudes and practices towards the prevention of malaria among the residents of the Jazan region of Saudi Arabia. Methods : This was a community-based cross-sectional survey using a structured questionnaire that was developed and distributed among 600 randomly selected households (≥18 years) from 11 sub-regions located in Jazan region of Saudi Arabia. The collected data were analyzed using Stata 15. Results : The majority of respondents were aware that malaria is a deadly disease transmitted by mosquito bites. They were familiar with malaria symptoms and common source of information. Indoor residual spraying (IRS) was the most popular preventive measure, practiced by 68.2% of respondents, followed by repellent and mosquito bed nets. Most respondents indicated that they would prefer to seek malaria treatment from healthcare facilities (80.3%) instead of pharmacy or other alternatives. The level of knowledge about malaria and its prevention differed significantly among various age and educational groups; however, no significant difference was observed across genders. Conclusions : There is appreciable knowledge about malaria symptoms, its transmission, and preventative methods among this Saudi Arabian population but there nevertheless remains a need for increased awareness of effective malaria prevention practices in certain areas. The outcome of the study highlights a growing need for generating innovative local strategies to improve preventative practices in order to meet malaria elimination goals.